Pengembangan Aplikasi Perangkat Bergerak Berbasis Android Dengan Kontrol Kepala Sebagai Alat Bantu Ujian Pada Siswa Tuna Daksa - Riski Puspa Dewi Diangga Putri; Lutfi Fanani; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Head Movement Control System (HEMOCS) is a method that changes the control of objects on the system using head movement. In the field of education, apps for answering exam using the head movement control applied to the android platform can help disabled students to answer the exam. This application changes the function of hand-based input into head-based. Using Head Mounted Display (HMD) this application can be controlled with six single motions of lateral rotation to the right, lateral rotation to the left, lateral flexion right, lateral flexion left, flexion, extension and there are three combinations of rightward-rightward, leftward-leftward and downward-downward. Development of this application using the method of SDLC Prototyping, which iterated twice to get the needs in accordance with the user. Furthermore based on the design obtained, performed the implementation phase of the system. Based on the test conducted reusability obtained results of 80,5 which indicates that the application is easy to use by the user.